2014
DOI: 10.14202/vetworld.2014.49-51
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and haemato-biochemical alterations in cattle of Jammu suffering from anaemia

Abstract: Aim: To obtain the clinical appraisal and haemato-biochemical alterations in cattle suffering from anaemia in Jammu division of J&K, India. Materials and Methods:125 cattle were screened for anaemia on the basis of Haemoglobin (Hb) concentration. Blood samples were taken for estimation of Hb, packed cell volume (PCV), total erythrocyte count (TEC), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), total protein, albumin, total bilirubin, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
4
5
0
2
Order By: Relevance
“…This might be due to damage caused by the heamoprotozoan organisms inside the RBC's during their multiplication (Soulsby, 1982). The present report of haematological alternation in haemoprotozoan infection is in conformity with the observation made by earlier workers (Muraleedharan et al, 2005;Singla et al, 2013;Singh et al, 2014).The data for the hematological parameters for suspected animals are coming within the range of normal and infected animals with high standard error (SE). This shows the very high animal to animal variation.…”
Section: Analysis Of Hematological Parameterssupporting
confidence: 93%
“…This might be due to damage caused by the heamoprotozoan organisms inside the RBC's during their multiplication (Soulsby, 1982). The present report of haematological alternation in haemoprotozoan infection is in conformity with the observation made by earlier workers (Muraleedharan et al, 2005;Singla et al, 2013;Singh et al, 2014).The data for the hematological parameters for suspected animals are coming within the range of normal and infected animals with high standard error (SE). This shows the very high animal to animal variation.…”
Section: Analysis Of Hematological Parameterssupporting
confidence: 93%
“…Similarly, antigens of the BVD-MD vaccine seem to elicit antibodies that bind not only to peripheral blood observed in young animals, because of their rapid growth and the large amount of iron needed for the production of hemoglobin, myoglobin and other ironcontaining compounds (Green et al, 1997) as well as in ewes after parturition (Cihan et al, 2016). The most frequent cause of iron deficiency is endo-and ectoparasitism (Singh et al, 2014). However, iron is also implicated in the pathogenesis of anemia of the chronic disease.…”
Section: Hemolytic Anemiamentioning
confidence: 99%
“…Anemia is functionally defined as decreased oxygen carrying capacity of blood. This condition is clinically characterized by reduction in the HGB, hematocrit or RBC per unit volume of blood in a normally hydrated animal (22). In the present study, the comparison of some hematological parameters between both groups revealed that WBC and HGB were negatively affected, and were potentially manifested by clinical signs (anemia) as a result of the hematophagous ticks.…”
Section: Discussionmentioning
confidence: 43%